Effect of Liquid Organic Fertilizer from Capra aegagrus hircus on Vitamin A from Lactuca sativa using the Deep Flow Technique System - Cut Rahma Diana; Hafnati Rahmatan; Supriatno Supriatno (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2020)
This study aims to determine the effect of fertilizer application on the vitamin A content of lettuce plants. This type of research is experimental research. This research was carried out in Lambada Lhok village and in the Biology Education Laboratory of FKIP Syiah Kuala University. This study used a Completely Randomized Design (CRD) method with 4 levels of treatment and 6 repetitions to obtain 24 experimental units. Data were analyzed statistically using Variant Analysis (ANAVA) and if there were significant differences between one treatment with another, then further tests were carried out. Based on the results of research on the provision of liquid organic fertilizer (POC) local bean goat (Capra aegagrus hircus) has a significant effect on the vitamin A content of lettuce (Lactuca sativa). The optimum vitamin A content is in the P2 treatment with a concentration of 35% Liquid Organic Fertilizer.